2008
DOI: 10.1016/j.ejheart.2008.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trials update from European Society of Cardiology meeting 2008: TIME‐CHF, BACH, BEAUTIFUL, GISSI‐HF, and HOME‐HF

Abstract: This article provides information and a commentary on trials relevant to the pathophysiology, prevention and treatment of heart failure presented at the European Society of Cardiology meeting which was held in Munich, Germany from 30th August to 3rd September 2008. Unpublished reports should be considered as preliminary, as analyses may change in the final publication.The TIME-CHF study failed to show that BNP guided therapy was superior to usual care in patients with heart failure. The BACH study suggested th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…The greatest benefits are seen in younger patients with systolic heart failure, in whom reductions in mortality and heart failure events have been demonstrated with peptide-guided therapy (53)(54)(55).…”
Section: Monitoring Of Heart Failurementioning
confidence: 96%
“…The greatest benefits are seen in younger patients with systolic heart failure, in whom reductions in mortality and heart failure events have been demonstrated with peptide-guided therapy (53)(54)(55).…”
Section: Monitoring Of Heart Failurementioning
confidence: 96%
“…43 The results of GISSI-Prevenzione were supported by the finding of a reduction in mortality and death or cardiovascular hospitalizations in GISSI-HF. 2,44 However, these studies suggested little effect during the first year of follow-up.…”
Section: Presented By Bengt Fellstrom From Uppsala Swedenmentioning
confidence: 98%
“…However, the results of a recent systematic review of the effect of fish oil on the incidence of arrhythmias and mortality found that despite a reduction in cardiac deaths, fish oil (Ω‐3 fatty acids, n‐3 polyunsaturated fatty acids) supplementation had no effect on arrhythmias or all‐cause mortality . The results of GISSI‐Prevenzione were supported by the finding of a reduction in mortality and death or cardiovascular hospitalizations in GISSI‐HF ,. However, these studies suggested little effect during the first year of follow‐up.…”
Section: Omega: Randomized Trial Of Omega‐3 Fatty Acids On Top Of Modmentioning
confidence: 99%
“…GISSI-HF concluded that a simple and safe treatment with n-3 PUFA can provide a small beneficial advantage in terms of mortality and admission to hospital for cardiovascular reasons in patients with heart failure. In the GISSI-HF sub-analyses of patients randomly assigned to rosuvastatin 10 mg daily (n = 2285) or placebo (n = 2289) using primary endpoints of time to death, and time to death or admission to hospital for cardiovascular reasons, 657 (29%) patients died from any cause in the rosuvastatin group and 644 (28%) in the placebo group (adjusted HR 1.00, 95.5% CI: 0.898–1.122; p = 0.943), with a final conclusion that rosuvastatin 10 mg daily did not affect clinical outcomes in patients with chronic heart failure of any cause 97. Whether higher doses have different effects need to be clarified.…”
Section: Af In Left Ventricular Dysfunctionmentioning
confidence: 97%